Small ribonucleoproteins in Schizosaccharomyces pombe and Yarrowia lipolytica homologous to signal recognition particle. - Poritz, M A (1988)
We have partially purified ribonucleoproteins (RNPs) from Schizosaccharomyces pombe and Yarrowia lipolytica with properties resembling those of mammalian signal recognition particle (SRP). In both species of yeast we have identified a single major RNA species in the size range of SRP RNA (256 nucleotides in S. pombe and 270 nucleotides in Y. lipolytica) present in postribosomal salt extracts of the cytoplasm. The RNPs containing these RNAs sediment in sucrose gradients at 11 S and 10 S for S. pombe and Y. lipolytica, respectively. Analysis of genomic clones of these RNAs has revealed that (i) they are encoded by single copy genes; (ii) they share two short conserved sequences that match the A and B boxes defined for polymerase III promoters; (iii) they can be folded into secondary structures that closely match that defined by phylogenetic analysis of higher eukaryotic SRP RNAs; and (iv) they show primary sequence conservation in short regions predicted to be single stranded. Both of the yeast RNAs bind under stringent conditions to canine SRP proteins. Most importantly, RNase protection of the S. pombe RNA by the individual canine SRP proteins, p19 and p68/72, shows that the proteins recognize homologous elements of the mammalian and yeast RNA. Taken together these data suggest strongly that we have identified yeast SRP homologues.